The optimal whole body vibration frequency effects on postural responses in soccer players - Fiorilli, G.; Iuliano, E.; Giombini, A.; Casasco, M.; Fagnani, F.; Quinzi, F.; Buonsenso, A.; Pigozzi, F.; Di Cagno, A.; Calcagno, G. (Sport Sciences for Health, 2020)
Purpose: To verify if pre-performance vibration exposure could negatively affect the postural control in soccer players. Methods: Twenty-eight participants, 12 male soccer players (aged 22.4 ± 1.0 years) and 16 sedentary males (aged 26.8 ± 2.7 years), underwent two test sessions: in the first one, the optimal vibration frequency (OVF) was determined for each participant, and in the second one, postural sways, with open and closed eyes, were assessed at baseline, immediately, 10, 20 min after the WBV exposure. The vibration exposure consisted in five sets of 1 min each one, at OVF, with 1-min rest between each set. Results: The elliptical area, containing the 95% of the centre of pressure (COP), displacements (AREA), the total linear distance covered by the COP (LENGTH), the average distance between the assessed COP position and the ideal COP position (AV-DIST) and variance of speed of the COP displacements (VAR-SPEED), have been analysed. RM-ANOVA did not show significant differences among the times of assessment. Significant differences in all the dependent variables, between the groups, especially in closed eyes condition, were found. Athletes with closed eyes showed a significantly smaller COP AREA (p = 0.00004), minor AV-DIST (p = 0.0001), which are good indicators of an optimal postural control. Conclusion: An acute bout of WBV at the OVF did not modify the COP parameters and may be used before the performance, with no side effect on balance. Athletes have developed a postural strategy on non-visual afferent inputs that could be enhanced by the WBV chronic exposure.